The History of the Polish People’s Republic According to Wojciech Smarzowski: An Interpretation - Szpulak, Andrzej (Media - Culture - Social Communication, 2019)
The text is focused on interpreting three films of Wojciech Smarzowski: Wesele (Weddings, 2004), Dom zły (Bad House, 2009) and Róża (Rose, 2011). These films are treated as audio-visual historical narrations presenting the reality of communist Poland (1945–1989) along with the social consequences of living in conditions imposed by the post-Communist state after 1989. This reality is analysed at the political, social, economic and spiritual levels. The idea is to grasp historical continuity, present in these narrations, which depends on the chronology of the works of the movie director. A theoretical basis for reflection is the visual history concept, referred to by Piotr Witek (Andrzej Wajda as a Historian) based, above all, on the reflections of Robert A. Rosenstone.